Assessment of the Impact of APEX1 (rs2307486) and URAT1 (rs11231825) Gene Polymorphisms on the Response of Hypouricemic Therapy in Women with Gout - Qizi, Tashpulatova Maktuba Mukhamedali; Abdumalikovna, Nabiyeva Dildora (Journal of Advances in Medicine and Medical Research, 2025)
This scientific study aimed to evaluate the effect of polymorphisms in the APEX1 (rs2307486) and URAT1 (rs11231825) genes on the effectiveness of hypouricemic therapy in women with gout. The study included 102 female patients as the primary analysis group and 100 male patients with gout as a secondary comparative cohort in 2021–2024. The patients were prescribed allopurinol and febuxostat, and their effectiveness was assessed across different genotypes of the above genes. According to the results of the study, patients with the G/G genotype of the APEX1 gene had a low response to allopurinol, and only febuxostat was effective. In patients with the T/T genotype, both drugs were almost equally effective. In patients with the T/T genotype of the URAT1 (rs11231825) gene, resistance to allopurinol and a requirement for a higher dose were found, and febuxostat was noted to be more effective. In patients with the A/A genotype, the standard dose was sufficiently effective. These results indicate that polymorphisms of the APEX1 and URAT1 genes are important pharmacogenetic biomarkers in determining the individual effectiveness of hypouricemic therapy. The selection of drugs and their doses based on a personalized approach increases therapeutic efficacy, eliminates resistance, and improves quality of life.